Exchange rates and economic policy in the 20th century - Aldcroft, Derek Howard; Catterall, Ross, 1948- (Modern economic and social history series, 2004)
"The themes of this study are the exchange rate regimes chosen by policy-makers in the 20th century, the means used to maintain these regimes, and the impact of these decisions on individual national economies and the world economy in general. The book draws heavily on new research showing the lessons and the legacy left for policy makers by the gold standard and the attempt at its resurrection in the 1920s. In examining issues such as the gold exchange standard, the gold bullion standard, the experience of floating exchange rates, the Bretton Woods arrangements, the EMS and the ERM, and the Currency Board approach, there is a conscious attempt to draw out the relevance of history for policy-makers now."--BOOK JACKET.